The Entrepreneur Innovation, and Learning Orientation as Antecedents of Global Purchasing: Does the Environmental Turbulence Matter in Thai Import Oriented Industries? - Jetsalid Anesukanjanakul; Chonticha Somjai; Chandej Charoenwiriyakul; Teepakorn boonaram (International Journal of Supply Chain Management, 2019)
The study is planned to examine the impact of entrepreneur innovation and learning orientation on the global purchasing of firms in the five biggest import industries of Thailand. To have a more detailed insight the study has incorporated the two factors from environmental turbulence namely market turbulence, and technological turbulence as moderator. The study has used the PLS-SEM to answer the research questions. PLS-SEM has become an advanced alternative to previous co-variance approaches because of its unique features and abilities. PLS-SEM technique is the widely adopted approach and it has gained huge recognition among the researchers. The findings of the study have provided me the support to the hypotheses result. From the findings it has been found by this study that the organizations, which operate in environment with technological turbulence, possess a strong association between entrepreneurial innovation and learning orientation as compared to less turbulent organizations. There is need for managers to be aware of the level of technological change, which affects the influence of innovation and learning on purchasing performance. There is need for managers to emphasize on learning while operating in highly turbulent technological environment to foster innovation by developing long-term associations with suppliers.